Physical and psychological correlates of high somatic symptom severity in Chinese breast cancer patients. Issue 5 (2nd August 2016) - Leonhart, Rainer; Tang, Lili; Pang, Ying; Li, Jinjiang; Song, Lili; Fischer, Irmela; Koch, Maike; Wuensch, Alexander; Fritzsche, Kurt; Schaefert, Rainer
Abstract: Objective: We researched associations between somatic symptom severity (SSS), and physical and psychological factors in Chinese breast cancer patients. Methods: This multicenter cross‐sectional study enrolled 255 Chinese breast cancer patients of different stages and treatment phases. They answered standard instruments assessing SSS (Patient Health Questionnaire [PHQ]‐15), depression (PHQ‐9), anxiety (General Anxiety Disorder [GAD]‐7), health anxiety (Whiteley‐7 [WI‐7]), illness perception (Brief‐Illness Perception Questionnaire [IPQ]), illness attribution (Illness Perception Questionnaire‐Revised [IPQ‐R]), and sense of coherence (Sense of Coherence [SOC]‐9). Logistic regression was applied to identify the strongest correlates with SSS. Results: Our sample of high (PHQ‐15 ≥ 10) and low SSS differed significantly in the following physical and psychological variables: symptom duration ( r = 0.339, P < .001), symptom‐related disability (Karnofsky Index) ( r = 0.182, P < .001), depression ( r = 0.556, P < .001), anxiety ( r = 0.433, P < .001), health anxiety ( r = 0.400, P < .001), illness perception ( r = 0.349, P < .001), psychological illness attributions ( r = 0.217, P < .01), and sense of coherence ( r = −0.254, P < .001). In an adjusted stepwise multiple binary logistic regression analysis, higher health anxiety (WI‐7, B = 0.388, P = .002), higher depression (PHQ‐9, B = 0.158, P < .001), younger age ( B = −0.042, P = .048), higher impairment in daily life ( B = 1.098, P = .010), and longer symptom duration (Wald = 18.487, P = .001) showed a significant association with high SSS; the model explained 55.1% of the variance. Conclusions: High somatic symptom burden in breast cancer is associated with physical and psychosocial features. The results are a basis for further research to evaluate the new Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, SSD concept in cancer patients and to better operationalize psychobehavioral factors in this patient group.